The clinical implications of mouse models of enhanced anxiety. (July 2011) - Sartori, Simone B; Landgraf, Rainer; Singewald, Nicolas
Mice are increasingly overtaking the rat model organism in important aspects of anxiety research, including drug development. However, translating the results obtained in mouse studies into information that can be applied in clinics remains challenging. One reason may be that most of the studies so far have used animals displaying ''normal'' anxiety rather than ''psychopathological'' animal models with abnormal (elevated) anxiety, which more closely reflect core features and sensitivities to therapeutic interventions of human anxiety disorders, and which would, thus, narrow the translational gap. Here, we discuss manipulations aimed at persistently enhancing anxiety-related behavior in the laboratory mouse using phenotypic selection, genetic techniques and/or environmental manipulations. It is hoped that such models with enhanced construct validity will provide improved ways of studying the neurobiology and treatment of pathological anxiety. Examples of findings from mouse models of enhanced anxiety-related behavior will be discussed, as well as their relation to findings in anxiety disorder patients regarding neuroanatomy, neurobiology, genetic involvement and epigenetic modifications. Finally, we highlight novel targets for potential anxiolytic pharmacotherapeutics that have been established with the help of research involving mice. Since the use of psychopathological mouse models is only just beginning to increase, it is still unclear as to the extent to which such approaches will enhance the success rate of drug development in translating identified therapeutic targets into clinical trials and, thus, helping to introduce the next anxiolytic class of drugs.